Insights on climate peace, social cohesion and mobility in Namibia - Sigopi, Maria; Makanda, Joseph; Maviza, Gracsious; Tarusarira, Joram; Amutenya, Klaudia; Thompson, Sylvia; Joao, Baptista; Hamukwaya, Panduleni (2025)
Climate change is having alarming effects on societies and ecosystems. There is also growing evidence of its impacts transforming and redefining the global peace and security landscape across local, national, and international levels. These impacts are triggering competition over natural resources, compromising livelihoods, and causing displacement, thereby increasing the risk of social tensions and instability